Ответ:
x = 0,3
Пошаговое объяснение:
а) 2(0,2 - x) = x - 0,5;
Раскрываем скобки в первой части уравнения:
2*0,2 - 2x = x - 0,5
-2x - x = -0,5 - 0,4
-3x = -0,9
x = -0,9:(-3) = 0,3
Проверка:
2(0,2 - 0,3) = 0,3 - 0,5
2(-0,1) = -0,2
-0,2 = -0,2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
x = 0,3
Пошаговое объяснение:
а) 2(0,2 - x) = x - 0,5;
Раскрываем скобки в первой части уравнения:
2*0,2 - 2x = x - 0,5
-2x - x = -0,5 - 0,4
-3x = -0,9
x = -0,9:(-3) = 0,3
Проверка:
2(0,2 - 0,3) = 0,3 - 0,5
2(-0,1) = -0,2
-0,2 = -0,2